Analytical Method Optimization of H₂O₂ Derivatization Reaction Time for HPLC Analysis under Tropical Laboratory Conditions - Dinalia; Husain Sosidi; Ahmad Ridhay; Hannan Hannan; Khairuddin Khairuddin; Pasjan Satrimafitrah; Syamsuddin Syamsuddin (Journal of Chemical Learning Innovation, 2026)
Purpose of the study: This study aims to evaluate the suitability of the commonly reported 2-hour derivatization time for hydrogen peroxide (H₂O₂) determination using HPLC-PDA by assessing the formation behavior of triphenylphosphine oxide (TPPO) under tropical laboratory conditions. Methodology: The study employed an HPLC–PDA system (Shimadzu LC-20AD) with a reversed-phase C18 column (Waters X-Bridge, 4.6 × 150 mm, 5 µm). Derivatization of H₂O₂ with triphenylphosphine (Sigma-Aldrich) was performed using acetonitrile (Merck). The time-dependent kinetics of TPPO formation were evaluated based on chromatographic peak area monitoring. Data were processed using integrated instrument software. Main Findings: The TPPO peak area increased progressively with reaction time and approached a plateau at approximately 60 min, indicating near-complete derivatization under the studied conditions. No substantial increase in analytical response was observed at longer reaction times. Repeatability evaluation at 60 min showed acceptable analytical precision with %RSD below 2%, demonstrating that a shorter derivatization time was adequate for routine analysis. Novelty/Originality of this study: This study provides a context-specific evaluation of derivatization time as part of analytical method optimization in HPLC systems under tropical laboratory conditions. The findings demonstrate the importance of verifying derivatization parameters under specific working environments to improve analytical efficiency and ensure reliable chromatographic performance.